An Analysis of the Influence of Oil and Gas Revenue Sharing Funds, World Oil Price, Local Tax, Local Expenditures, and Capital Expenditures on the Fiscal Capacity of Bojonegoro Regency During the 2001-2024 Period - Ine Hanindya, Lingga; Suryo Bintoro, Nugroho (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study analyzes the effects of Oil Revenue Sharing (DBH Migas), world oil prices, regional taxes, regional expenditures, and capital expenditures on the fiscal capacity of Bojonegoro Regency from 2001 to 2024, using the Vector Error Correction Model (VECM). The results show that in the long term, DBH Migas, world oil prices, and regional taxes have a significant impact on fiscal capacity, while regional and capital expenditures do not. In the short term, all variables significantly affect fiscal capacity, especially DBH Migas and world oil prices at certain lags. The error correction term (ECT) is negative but not significant, indicating a slow adjustment toward long-term equilibrium.